Book review: Flaschel, Peter and Alfred Greiner (2012): Flexicurity Capitalism: Foundations, Problems, and Perspectives, New York (240 pages, hardcover, Oxford University Press, ISBN 978-0-19-975158-7) - Yun K. Kim (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2013)
This book provides an important discussion of an alternative form of capitalism, flexicurity capitalism. Flexicurity capitalism emphasizes labor market flexibility such as the freedom of firms to fire and hire workers but also ensure that workers can obtain a job and income via institutional setup to avoid human degradation due to unemployment. Flexicurity capitalism could solve important economic problems such as coordination and incentive problems, the problems traditional socialist society experienced (which the authors call Eastern type socialism). Flexicurity capitalism opens the possibility of a more humane form of capitalism, which is more competitive and flexible than a traditional socialist society.
Keywords: 330